Direct monthly highly active antiretroviral therapy supply – a method to increase patient's adherence and outcome. Experience of one AIDS centre in Israel. (July 2014) - Elbirt, Daniel; Asher, Ilan; Mahlev-Guri, Keren; Bezalel-Rozenberg, Shira; Werner, Ben; Cohen, Yafa; Sthoeger, Zev
In Israel, antiretroviral therapy (ART) is available (at local pharmacies) without cost. Nevertheless, poor adherence, especially of immigrants from Africa, leads to a high rate of treatment failures. Our study looked whether direct monthly ART supply in our AIDS centre has an effect on adherence and outcome. A total of 385 HIV (clade C) immigrants from Africa that were treated with ART for >2 years prior to the initiation of the study were evaluated. During the first 2 years, ART medications were supplied by local pharmacies. Thereafter (next 2 years), all patients received medications, monthly at our centre. Adherence, immunological (CD4) and virological (VL) outcome at the end of the two study periods were determined. At baseline, only 75% of the patients attended more than 90% of scheduled visits with 57% treatment adherence. Virological failure (VL >40 copies/ml) was observed in 53% of the patients. As a result of our intervention (2 years of direct monthly ART supply), visits and treatment adherence significantly increased (90% and 84%, respectively; p < 0.001). Concomitantly, virological failure rate significantly dropped to 28% ( p < 0.001). Direct monthly supply of ART is a relatively low-cost mode to improve patient's adherence and immunological/virological outcomes.